Rights and Requests of Citizens in the Social Field (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The essence of this scientific article is that the Constitution of the Republic of Uzbekistan details the rights and obligations of citizens living in the Republic of Uzbekistan and the measures to implement them, as well as the essence of the articles contained in the law.